The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jbm.a.35056
|View full text |Cite
|
Sign up to set email alerts
|

Periostin improves cell adhesion to implantable biomaterials and osteoblastic differentiation on implant titanium surfaces in a topography-dependent fashion

Abstract: Periostin is a matricellular protein highly expressed in periodontal ligament and periostium and has been shown to be required for tissue development and maintenance. We showed that the adhesion of murine osteoblastic MC3T3 cells to thiolated hyaluronic acid/polyethyleneglycol hydrogels was greatly improved by enrichment with periostin. Polished or sand-blasted/acid-etched (SLA) commercially pure titanium surfaces were also coated with this protein and periostin ameliorated cell adhesion and dramatically affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The function of POSTN as an ECM protein in bone formation has been determined recently. POSTN is a secreted protein that is highly expressed in MSCs/preosteoblasts and supports cell adhesion, spreading, and differentiation [ 18 ]. In addition, expression of integrin α v β 3, the receptor of POSTN, has been observed in MSCs/preosteoblasts [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The function of POSTN as an ECM protein in bone formation has been determined recently. POSTN is a secreted protein that is highly expressed in MSCs/preosteoblasts and supports cell adhesion, spreading, and differentiation [ 18 ]. In addition, expression of integrin α v β 3, the receptor of POSTN, has been observed in MSCs/preosteoblasts [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Artificial matrices derived from tissues with cells either lacking or overexpressing a particular matricellular molecule could direct host cellular responses via alteration of tissue repair processes such as angiogenesis, matrix assembly, and myofibroblast induction ( Barker et al, 2005b ; Elliott et al, 2012 ; Calabro et al, 2014 ; Morris and Kyriakides, 2014 -in this issue). For example, coating either smooth or etched titanium implants with periostin increased cell adhesion as compared to metal surfaces without periostin, although periostin only improved osteoblastic differentiation of cells adherent to smooth titanium surface, suggesting that perhaps the surface bound conformation of periostin can differentially regulate cell behavior ( Galli et al, 2013 ). One can also take advantage of sequence-specific matricellular interactions with growth factors or receptors to target molecules to biologic scaffolds: one of the TGF-β binding motifs of TSP-1 (GGWSHW) was coupled to a scaffold to localize TGF-β to hydrogels for local growth factor delivery ( McCall et al, 2011 ).…”
Section: Matricellular Proteins In Tissue Engineering and Responsementioning
confidence: 99%
“…Interestingly, Postn is highly expressed in human BMSCs and their derived adipocytes, chondrocytes, and osteoblasts [26,27]. Postn is a secreted protein that is highly expressed in MSCs/preosteoblasts and supports cell adhesion, spreading, and differentiation [28]. Heo et al [29] found that delivery of recombinant Postn to human adipose tissue-derived MSCs embedded within a hydroxyapatite/tricalcium phosphate scaffold can accelerate healing of calvarial defects.…”
Section: Discussionmentioning
confidence: 99%